1991
DOI: 10.2307/1542389
|View full text |Cite
|
Sign up to set email alerts
|

Computation in the Learning System of Cephalopods

Abstract: The memory mechanisms of cephalopods consist of a series of matrices of intersecting axes, which find associations between the signals of input events and their consequences. The tactile memory is distributed among eight such matrices, and there is also some suboesophageal learning capacity. The visual memory lies in the optic lobe and four matrices, with some re-exciting pathways. In both systems, damage to any part reduces proportionally the effectiveness of the whole memory. These matrices are somewhat like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
111
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(112 citation statements)
references
References 9 publications
1
111
0
Order By: Relevance
“…The lack of information on behaviour in nautilus represents a gap in our knowledge of learning among the molluscs, yet nautilus is a particularly interesting subject for studies of the evolution of dedicated learning structures, primarily because of its close relationship to the coleoids, the most neurologically complex invertebrates. It is the oldest and most primitive of the extant cephalopods (Saunders et al, 1996) and is the only extant cephalopod lacking the vertical lobe complex (Young, 1965;Young, 1991). Therefore identifying similar behavioural abilities in nautilus to those known in other cephalopod and non-cephalopod molluscs should shed considerable light on the evolutionary pathways that led to the development of the complex coleoid brain, and on general principles underlying the evolution of neural complexity.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The lack of information on behaviour in nautilus represents a gap in our knowledge of learning among the molluscs, yet nautilus is a particularly interesting subject for studies of the evolution of dedicated learning structures, primarily because of its close relationship to the coleoids, the most neurologically complex invertebrates. It is the oldest and most primitive of the extant cephalopods (Saunders et al, 1996) and is the only extant cephalopod lacking the vertical lobe complex (Young, 1965;Young, 1991). Therefore identifying similar behavioural abilities in nautilus to those known in other cephalopod and non-cephalopod molluscs should shed considerable light on the evolutionary pathways that led to the development of the complex coleoid brain, and on general principles underlying the evolution of neural complexity.…”
Section: Introductionmentioning
confidence: 98%
“…The thirteen main lobes are not clearly differentiated from the surrounding tissue (Young, 1965) and there appears to be little specialisation. The vertical and subfrontal lobes, regions of the brain that have been implicated in tactile and visual learning and memory in coleoids (Young, 1960;Young, 1961;Hochner et al, 2003) are entirely absent from the nautilus CNS (Young, 1965), and there is some evidence that the structural simplicity of the brain may be representative of an ancestral condition (Young 1991;Shigeno et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Various researchers have suggested that this tract, which shows a matrix-like organization between the vertical lobe, appears to be analogous to vertebrate brain structures involved in learning and memory (e.g. the hippocampus and cerebellum) (Young 1995), and to insect mushroom bodies (Young & Boycott 1955, Young 1991, Hochner et al 2006, Hochner 2010. Among cellular processes, a robust, activitydependent long-term potentiation (LTP) underlying the physiological basis of learning and memory that resembles some aspects of vertebrate LTP is shown in this tract.…”
Section: Gaba In Learning and Memorymentioning
confidence: 99%
“…Reports of relationships between sociality and neuronal mechanisms in invertebrates are scarce. However, the GABAergic elements expressed in the tract between the superior frontal lobe and the vertical lobe may play a role in cognitive behaviors such as social interaction, because there are similarities between the hippocampus of the vertebrate brain and the vertical lobe of the cephalopod brain in which abundant GABAergic elements were detected (Young 1991, Hochner et al 2003.…”
Section: Possible Role Of Gaba In Socialitymentioning
confidence: 99%
“…There is also some indication that the nociceptor rate of firing or sensitivity is related to the sensitivity of the tissue that they protect (Mather 2004). Cephalopods can learn to avoid putatively painful stimuli (Young 1991), and have many of the neurotransmitters that are involved in vertebrate pain reception and mediation (Abbott et al 1995).…”
Section: Sentience Awareness and Animal Welfarementioning
confidence: 99%